Undergraduate Academic Probation Policies in U.S. Universities: A Policy Discourse Analysis - Barouch-Gilbert, Abraham (Alberta Journal of Educational Research, 2022)
This paper explores undergraduate academic probation policies in United States universities from a policy discourse analysis perspective. Academic probation policies from 32 institutions were characterized by normalization and regulation. These encompassed classification, exclusion, and sanctions of students in order to produce retention. Consideration needs to be given to existing academic probation policies as discourse, their origins, the social identities, and particular realities that are being constructed by them. Institutions should question if academic probation policies are truly aligned with student retention to avoid these policies being an obstacle itself to student retention. Keywords: academic probation policy, higher education, critical discourse analysis, student retention. Cet article explore les politiques de probation académique des étudiants de premier cycle dans les universités américaines dans une perspective d'analyse du discours politique. Les politiques de probation académique de 32 institutions sont caractérisées par la normalisation et la régulation. Elles englobent la classification, l'exclusion et les sanctions des étudiants afin de favoriser la rétention. Il est nécessaire de prendre en considération les politiques de probation académique existantes en tant que discours, leurs origines, ainsi que les identités sociales et les réalités particulières qu'elles construisent. Les institutions devraient se demander si les politiques de probation académique sont réellement alignées sur la rétention des étudiants afin d'éviter que ces politiques ne soient elles-mêmes un obstacle à la rétention des étudiants. Mots clés : politique de probation académique, enseignement supérieur, analyse du discours critique, persévérance scolaire